Analisis Hukum Islam Mendapatkan Gift Pada Konten Self Harm di Live Apk Tiktok Perspektif DSN MUI No 24 Tahun 2017 Tentang Hukum dan Pedoman Bermuamalah Melalui Media Sosial - Ahmad Fauzan; Muhammad Amar Adly (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The research method used is normative law, which is research that examines legal documents as the main source with a qualitative descriptive approach. Data was collected through a literature study covering fatwas, books, journals, and related documents. The results of the study show a phenomenon of misuse of the live streaming feature in the TikTok application, specifically by displaying self-harm content in order to obtain gifts from viewers, which is haram because it contradicts the words of Allah in QS AL-Baqarah 195. This practice not only violates moral values but also contravenes the principles of Sharia. Furthermore, this action contradicts the main objectives of Islamic law (maqasid al-syariah), particularly in terms of protecting life (hifz al-nafs), intellect (hifz al-'aql), and property (hifz al-mal). Gift-giving in this context can no longer be categorized as a valid gift, as it is fraught with emotional manipulation and aims to support prohibited acts. Therefore, such transactions are not permissible under Islamic law and need to be regulated and monitored by the authorities to prevent them from continuing.